Pemberdayaan Kelompok Usaha Keripik Desa Kendalpayak Kecamatan Pakisaji Kabupaten Malang - Rusno Rusno; Yoyok Seby Dwanoko; Roni Alim. B. A (STIE Malangkucecwara, 2018)
Kendalpayak Village, Pakisaji Subdistrict, Malang Regency is a strategic and potential village to be made into the Central Village of Chips. There are two PKM partners in this village, namely: (1) a partner of the cassava chips group